What's New on the Internetz? Extraction and Lexical Categorisation of Collocations in Computer-Mediated Slovene. (4th February 2019) - Pollak, Senja; Gantar, Polona; Arhar Holdt, Špela
Abstract: The paper focuses on collocations typical of Slovene computer-mediated communication (CMC), which comprises communication via social networks, forums, blogs, etc. The study examines the CMC-specific collocates of the most frequent Slovene nouns, as well as collocates of CMC-typical nouns. Collocations were automatically extracted with procedures based on the Sketch Engine corpus tool. For the identification of CMC-specific collocations, collocates occurring in the CMC and the reference corpus were compared. In the study, the extracted data were categorised as: (a) new vocabulary in relation to existing lexicographical resources; (b) orthographically or lexically non-standard; (c) terminology; (d) topic-/genre-related. The new vocabulary was furthermore explored as per the distinction between new words, new collocations, and new meanings, where semantic shifts are of special interest. The results indicate that comparative collocation extraction provides a good framework for detecting lexical novelties and can thus provide good support for describing contemporary language use.